Transient development of gravity waves for two layered fluids - A. H. Essawy; M. S. Faltas (International Journal of Mathematics and Mathematical Sciences)
The transient gravity waves generated by a harmonically oscillating wave maker immersed in two incompressible fluids, the upper fluid having a free surface, is considered. The resulting linearized initial value problem is solved using the method of generalized functions, and asymptotic analysis for large time and distance are given for the elevation.